Smart Training Room and Its Impact on the Response Speed and Coordination of Goalkeepers of Handball Specialized Schools Ages (12-14) Years - Hussein Mahdi Salhe; Abbas Abdulhamza Kadhim; Hassim Abdul J abbar Salhe (Indian Journal of Forensic Medicine & Toxicology, 2021)
The researchers in this study resorted to designing a smart training room to prepare special exercises todevelop response speed, some movement abilities, and special basic skills of a goalkeeper, which are ofgreat importance for preparing goalkeepers, the aim of the research is to design a smart training room totrain goalkeepers of specialized schools at ages (12-14) years, and to prepare special exercises using thesmart training room to develop the speed of response for goalkeepers of specialized schools of handballunder the age of (12-14) years, and to identify the effect of special exercises. By using the smart trainingroom to respond quickly to goalkeepers of specialized handball schools under the age of (12-14) years.The researchers used the experimental approach to design the two equal groups in the pre and post-tests.The researchers identified the goalkeeper research community in the specialized schools in the centralEuphrates governorates affiliated with the Ministry of Sports and Youth, whose number is (25) goalkeepers,the researchers intentionally chose the Specialized School in Karbala Governorate and the late Zaki SabbarSchool, where the experimental group is the Specialized School with (6) guards, and the control group is thelate Zaki Sabbar School.